Vloga mariborskeg! Oddelka za geografijo pri razvoju slovenske didaktike geografije od druge polovice 20. stoletja do danes - Kolnik, Karmen (Revija za geografijo, 2013)
A short overview of fifty-year development of teaching geography in Maribor is introduced in three time periods: from the point of view of development of study programs, from initial two-year higher education study to todays five-year university, from the view of didactics of geography as one of the basic study programs of future geography teachers and from the view point of teaching and scientific part of holders and implementers of didactics of geography.
Keywords: didactic method; didaktika; Filozofska fakulteta; Filozofska fakulteta Maribor; geografija; geography; Maribor; metodika pouka; Oddelek za geografijo